М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
ninazaripova1
ninazaripova1
03.05.2020 07:16 •  Алгебра

1)sin(p/4-x) 2)sin(p/6+y) 3)cos(p/3-x) 4)tg(p/4-x)

👇
Ответ:
dance7
dance7
03.05.2020
1)sin(π/4-x)=sin(π/4)cosx-sinxcos(π/4)=(√2/2)cosx-sinx*√2/2=(√2/2)(cosx-sinx)
2)sin(π/6+y)=sin(π/6)cosx+sinxcos(π/6)=(1/2)cosx+sinx*(√3/2)(1/2)cosx+(√3/2)sinx
3)cos(π/3-x)=cos(π/3)cosx+sin(π/3)sinx=(1/2)cosx+(√3/2)sinx
4)tg(π/4-x) =(tg(π/4)-tgx)/(1+tg(π/4)tgx)=(1-tgx)/(1+tgx)
или если записать иначе
tg( \pi /4-x)= \frac{tg( \pi /4)-tgx}{1+tg( \pi /4)tgx}= \frac{1-tgx}{1+tgx}
4,4(79 оценок)
Открыть все ответы
Ответ:
Duhan1
Duhan1
03.05.2020
1) = 2+а+6+3а = 4а+8 = 4(а+2)
2) = 3 - а+6 - 2а = 9 - 3а = 3(3 - а)
3) = (m - n)(1 - 5) = - 4(m - n) = 4(n - m)
4) = (x - y)(1 - 4) = - 3(x - y)  = 3(y - x)
5) = (a+b)(4b+1)
6) = (x+y)(5x+1)
7) = (x-y)(a+1)
8)  = (m - n)(c+1)
9) = (a - b)+2(a - b) = (a - b)(1+2) = 3(a -b)
10) = (c - d)(1+3) = 4(c - d)
11) = 2(a - b)+c(a - b) = (a - b)(2+c)
12) = (c - d)(3 - a)
13) смотри 11
14) = (c - d) (3 +a)
15) = (x - e)(1+a)
16) = (m+n)(1+b)
17) = (x - y)(2+a)
18) = 3(m - n) - b(m - n) = (m - n)(3 - b)
19) = ([x+y)(2 - a)
20) = (m+n)(3 - b)
4,4(80 оценок)
Ответ:
azul1999
azul1999
03.05.2020
1) sin(45°+L)=sin(45°)*cos(L)+cos(45°)*sin(L)=√2/2*sin(L)+√2/2*cos(L)
2) cos(45°+L)=cos(45°)*cos(L)-sin(45°)*sin(L)=√2/2*cos(L)-√2/2*sin(L)
3) cos(3L) = cos(L)*cos(2L)-sin(L)*sin(2L) = cos(L)*(2cos²(L)-1)-sin(L)*2sin(L)*cos(L) = 2cos³(L)-cos(L)-2cos(L)*sin²(L) = 2cos³(L)-cos(L)-2cos(L)*(1-cos²(L)) = 2cos³(L)-cos(L)-2cos(L)+2cos³(L) = 4cos³(L)-3cos(L)
4) sin(3L) = sin(L)*cos(2L)+sin(2L)*cos(L) = sin(L)*(1-2sin²(L))+2sin(L)*cos(L)*cos(L) = sin(L)-2sin³(L)+2sin(L)*cos²(L) = sin(L)-2sin³(L)+2sin(L)*(1-sin²(L)) = sin(L)-2sin³(L)+2sin(L)-2sin³(L)=3sin(L)-4sin³(L)
4,8(96 оценок)
Это интересно:
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ